2022
DOI: 10.3390/ani13010089
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Marker-Assisted Selection of ABCG2, CD44, SPP1 Genes Contribute to Milk Production Traits of Chinese Holstein

Abstract: Based on our results of genome-wide association analysis, we performed gene ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis; three candidate genes (ABCG2, CD44, SPP1) were screened in this study for SNPs association analysis with production traits in 999 Holstein cattle. In this research, flight mass spectrometry genotyping was used to detect the polymorphism of SNP seats. It was shown that four, four, and two single nucleotide polymorphisms (SNP) loci we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We found a total of four SNPs (g.20491759G>A, g.20497651C>G, g.20499553G>C, and g.20500634T>A) in ANPEP, which have different allele frequencies in HM and LM goats. PRKG1 is located on goat chromosome 26 and has been suggested to be associated with milk fatty acid traits in Holstein cattle and swine (Li et al, 2014;Revilla et al, 2017;Shi et al, 2019). In our study, we identified an SNP (g.44250104T>G) in PRKG1 and found that mutated allele G at position 44 250 104 of the gene is more frequent in the high milk yield group than in the low milk yield group.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…We found a total of four SNPs (g.20491759G>A, g.20497651C>G, g.20499553G>C, and g.20500634T>A) in ANPEP, which have different allele frequencies in HM and LM goats. PRKG1 is located on goat chromosome 26 and has been suggested to be associated with milk fatty acid traits in Holstein cattle and swine (Li et al, 2014;Revilla et al, 2017;Shi et al, 2019). In our study, we identified an SNP (g.44250104T>G) in PRKG1 and found that mutated allele G at position 44 250 104 of the gene is more frequent in the high milk yield group than in the low milk yield group.…”
mentioning
confidence: 52%
“…One of the most important economic traits in goats is milk production, which is influenced by a variety of complex factors such as environmental temperature, nutrition, management practices, physiological state and genetics (Do et al., 2017). More and more studies have shown that single‐nucleotide polymorphisms (SNP) may cause a change in individual traits, such as growth, reproduction, milk production and other traits (Li et al., 2020; Sun et al., 2022). With the development of high‐throughput sequencing technology, whole‐genome resequencing has enabled the identification of the genomic variants generated during the selection process for domestic animals including SNPs.…”
Section: Trait Group N Mean ± Sd Minimum Maximum P‐valueamentioning
confidence: 99%
“…This phenomenon is welldocumented in dairy science.Additionally, studies like the one by [35]. in Sarda sheep and the study by [36].in Chinese Holstein cows have highlighted the statistically significant associations between various genetic variations in the SPP1 gene and milk components, particularly milk fat percentage. These findings suggest that the SPP1 gene plays a significant role in milk production and can influence variations in certain milk components .However, it's interesting to note that in the mentioned studies, other milk components such as lactose, protein, and non-fat solids were not significantly affected by the genetic variations in the SPP1 gene.…”
Section: 4relationship Between Spp1/snp4 Gene Polymorphism (G>a: P/41...mentioning
confidence: 97%
“…Several candidate genes have been identified for their associations with milk production traits. These genes include ABCG2, CD44, and SPP1, [10] ACADVL and IRF6, [11] and various genes identified through genome-wide association studies (GWAS) and RNA-sequencing [11]. These genes have been found to have significant genetic effects on milk yield, milk fat percentage, milk protein percentage and other milk production traits in dairy cattle.…”
Section: Marker Assisted Selectionmentioning
confidence: 99%